Zero Wastefor Creative Economy And Tourism In Kolo Asakota Village, Bima City - Solihin, Muhamad; Doo, Viona Febyola Refana; Huldi, Amzanatul; Mahya, WN. Marhamah; Aziz, Muhaimin; Yahya, Muhammad Rizal; Adriana, Novia; Al Munawarah, Nur; Nurhidayanti, Nurhidayanti; Rizkan, Rizkan; Hemon, A. Farid (Unram Journal of Community Service, 2024)
Garbage is a major problem in the development of beach tourism in Kolo Village, Bima City. Garbage causes beaches to become dirty, beaches become less beautiful, brings unpleasant odors, causes disease and environmental pollution. The results of observations of the state of waste in Kolo Village showed that the prominent waste problems are waste heaps, waste sources, waste sorting, waste storage/TPA, waste transportation, waste destruction, and low compliance/awareness of regional regulations regarding waste handling . The 2024 Mataram University PMD KKN program in Kolo sub-district aims to provide understanding to the community about the importance of the Zero Waste concept, digitize the promotion of Zero Waste Tourism and creative economy MSMEs, train community creativity in processing waste into craft products with selling value. Apart from that, the PMD KKN program is also to promote and maintain the cleanliness of tourist and residential environments. The results of the activity show that the Mataram University PMD KKN program in Kolo sub-district has influenced the community's enthusiasm for implementing zero waste and using recycled waste into products of economic value such as shopping bags (Z-Bags), key chains, and compost for agriculture. It is hoped that the Zero Waste concept will spur community creativity and develop a creative economy and waste-free tourism.